Identificación y proposición de prácticas de gerencia de alcance, en proyectos de desarrollo de software en Colombia (2017)
project management is a discipline that groups knowledge, techniques and tools that, when applied properly, makes such activities easier to operate and control , independently form operation in the organisations, but responsible of value generation for themselves, taking into account the restrictions from their context and reality. From this set, an important factor is scope management, givan that it defines the work that must be done, to satisfy the need that the project supplies through the final product, and takes special importance by being a decision source about the details that must (and must not) be done, giving an unique and clear specification of the factors and criteria contemplated in its production. This thesis seeks to go into greater detail in this area, with the particular focus on software development projects, which tipically are embraced in a highly dynamic environment: not only tools evolve constantly, but also changes in the needs, expectations and requirements rise with evident high frequency. This context leads to use more versatile management techniques, that might be perceived, in a first approach, as contradictions to the traditional definitions in project management. The thesis also tries to identify the common practices, used daily in the information technology (IT) industry, and determine the way in which such application leads to success, in order to suggest its implementation, even into other sectors, so it could raise the sucess rate of their projects. For this, it was used a cualitative approach, with descriptive character, which first required bibliographic revision of the main methodologies and standards in project management, such as PMBOK (Project Management Body of Knowledge). Next, a deeper revision was made for those standards, taking the best practices each one suggested. At the same time, a research of software developing process was made. With the advice of some expers in statistics, a survey was designed and applied to 115 people, who where related with project management, in order to find empirically the most common practices in this kind of projects. with the obtained data, three comparison varibales where defined: used methodology (agile or traditional), position (technical or management), and those who said their success rate was over 70%. With this definitions, differences and agreements were found. Additionally, three experts in software development project management were consulted, the findings and recommendations discovered, in order to verify the results against theory and practice, and getting new elements to take into account for the proposal of practices this work intends to do, which will be covered on chapter 10.